Relationship lending and the role of loan officers in China: Empirical analysis based on the data on companies in industrial clusters - Zhang, Cheng; Liu, Yu; Tang, Cheng (Edelweiss Applied Science and Technology, 2024)
Relationship lending refers to lending behavior in which a financial institution makes loan decisions based on the accumulated soft information on the borrower. Empirical studies have revealed the positive effect of relationship lending. However, questions concerning who generates and accumulates soft information and in what ways in China have never been analyzed empirically. This paper empirically aims to explain whether loan officers generate soft information in relationship lending using data collected through surveys conducted among SMEs in the apparel industry clusters in Zhejiang and Jiangsu provinces. Based on the results of this study, relationship banking in China, which deals with the role of loan officers, seems even more important than is generally recognized.